Teacher Professional Development In The Context Of Independent Learning - Riska Nadia (PT. Islamic Research Publisher, 2023)
To improve the quality of education and anticipate the demands of competence and learning in the era of the Industrial Revolution 4.0, The Ministry of Education and Culture of the Republic of Indonesia launched a policy known as “Merdeka Belajar